Artificial Intelligence Forces Us to Rethink Knightian Uncertainty: A Commentary on Townsend et al.’s “Are the Futures Computable?” - Ramoglou, Stratos; Schaefer, Reiner; Chandra, Yanto; McMullen, Jeff S. (Academy of Management Review, 2025)
[no abstract]